2015
DOI: 10.1097/igc.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors as Potential Therapeutic Agents in the Treatment of Granulosa Cell Tumors of the Ovary

Abstract: These findings implicate BRAF in the activated signaling responsible for the growth and viability of GCT and suggest that TKI already in clinical use may be a therapeutic option in the treatment of GCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
(42 reference statements)
1
12
1
Order By: Relevance
“…Although dasatinib primarily targets SRC and ABL, it also inhibits a variety of other tyrosine kinases, such as PDGFR and ephrin receptors [31]. Consistent with an earlier report of the effects of an SRC inhibitor in KGN cells [32], the present study showed that dasatinib strongly and selectively inhibited AGCT cell viability. Interestingly, dasatinib was effective in FOXL2-mutation positive AGCTs and the KGN cell line, whereas the responses in FOXL2 wild-type COV434 cells and hGL reference cells were significantly weaker.…”
Section: Discussionsupporting
confidence: 91%
“…Although dasatinib primarily targets SRC and ABL, it also inhibits a variety of other tyrosine kinases, such as PDGFR and ephrin receptors [31]. Consistent with an earlier report of the effects of an SRC inhibitor in KGN cells [32], the present study showed that dasatinib strongly and selectively inhibited AGCT cell viability. Interestingly, dasatinib was effective in FOXL2-mutation positive AGCTs and the KGN cell line, whereas the responses in FOXL2 wild-type COV434 cells and hGL reference cells were significantly weaker.…”
Section: Discussionsupporting
confidence: 91%
“…The associations of the mutated genes identified in the pathway analysis (Table 6) may broadly suggest pathways that may be targeted therapeutically. The association with EGFR signaling genes is particularly intriguing given first that the aGCT-derived KGN cell line exhibits constitutive activity of the MAPK pathway (26,27) through mechanisms that remain to be defined, and second that a high frequency of the TERT promoter mutation has been associated with tumor types that exhibit activation of MAPK signaling (6). The functional significance of the copy number changes requires further characterization, although the observed changes have previously been reported not to correlate with tumor stage or behavior (2,(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Currently treatment options, once surgery is no longer relevant, are limited [ 1 ]. Although there have been a number of studies which explore the role of various mitogenic signaling pathways in aGCT [ 4 7 ] the specific question of what differentiates stage 1 disease from advanced stage disease has not been explored.…”
Section: Introductionmentioning
confidence: 99%